Perception of healthcare social work practice by healthcare professionals during the COVID-19 pandemic. A study by the Costa del Sol Health Agency in Malaga, Spain - Gómez-Mora, Antonia; Munuera-Gómez, Pilar; Bódalo-Lozano, Esther; García-Navarro, Rosa María (Prospectiva. Revista de Trabajo Social e Intervención Social, 2026)
Health Social Work was considered as an essential profesional space in the context of COVID-19 to ensure the well-being of people. This research investigates the perception that interdisciplinary health professionals have about the Social Work professionals of the Costa del Sol Health Agency of the city of Málaga. (Spain). A quantitative methodology was used; it was developed through a descriptive design, using a structured questionnaire administered online during the second half of 2022 (n=246). The results obtained show revealed that the professional practice of Social workers working in the health field responds to a task of support, help, and collaboration that solves problems through empathy and coordination. Among the main conclusions, the relevance of this profession’s response in the hospital environment, that requires greater recognition in the healthcare field is highlighted.